Oncoprotein Stathmin Modulates Sensitivity to Apoptosis in Hepatocellular Carcinoma Cells During Hepatitis C Viral Replication. (2nd July 2018) - Lu, Nu T; Liu, Natalie M; Patel, Darshil; Vu, James Q; Liu, Lisa; Kim, Chae Yeon; Cho, Peter; Khachatoorian, Ronik; Patel, Nikita; Magyar, Clara E; Ganapathy, Ekambaram; Arumugaswami, Vaithilingaraja; et al.
Patients with chronic hepatitis C virus (HCV) infection risk complications of cirrhosis, liver failure, and hepatocellular carcinoma (HCC). Previously, our proteomic examination of hepatocytes carrying a HCV-replicon revealed that deregulation of cytoskeletal dynamics may be a potential mechanism of viral-induced HCC growth. Here, we demonstrate the effect of HCV replication on the microtubule regulator stathmin (STMN1) in HCC cells. We further explore how the altered activity or synthesis of stathmin affects cellular proliferation and sensitivity to apoptosis in control HCC cells (Huh7.5) and experimental HCV-replicon harboring HCC cells (R-Huh7.5). The HCV-replicon harboring HCC cells (R-Huh 7.5) lack viral structural genes/proteins for acute infectivity and thus is the standard model for in vitro chronic infection study. Knockdown of endogenous stathmin reduced sensitivity to apoptosis in replicon cells. Meanwhile, constitutively active stathmin increased sensitivity to apoptosis in replicon cells. In addition, overexpression of constitutively active stathmin reduced cell proliferation in both control and replicon cells. These findings implicate, for the first time, a novel role for stathmin in viral replication–related apoptosis. Stathmin's potential role in HCV replication and HCC make it a candidate for the future study of viral-induced malignancies.